Ujı aktıvıtas antıbakterı ekstrak etanol daun rambusa (Passiflora foetida L.) terhadap bakterı Pseudomonas aeruginosa - Sari Wijayanti; Heriani Heriani; Faizal Mustamin; Syuhada Syuhada (Politeknik Kaltara, 2022)
One of the medicinal plants in Indonesia is rambutan (Passiflora foetida L.). Some of the chemical substances contained in the leaves of rambusa include alkaloids, flavonoids, steroids, and triterpenoids which have an antibacterial effect. This study aims to determine the activity and concentration of effective antibacterial from the extract of rambutan leaves on the growth of Pseudomonas aeruginosa bacteria. The antibacterial test was carried out using disc diffusion or the Kirby method with test concentrations of 10%, 15%, 20%, and positive control (Ciprofloxacin). The results showed that the antibacterial inhibition of rambutan leaf extract concentrations of 10%, 15%, 20%, and positive control was 2.63 mm, 4.53 mm, 6.05 mm, and 26.72 respectively. The concentration of 20% of rambusa leaf extract showed moderate antibacterial activity with an inhibition zone diameter of 6.05 mm.